2012
DOI: 10.1002/rra.2619
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Riparian Tree Invasion on a Desert Stream

Abstract: Understanding mechanisms of exotic species' invasions is essential to managing riparian landscapes throughout the world. In the southwestern USA, the two most dominant invaders of riparian habitats are the exotic tree species tamarisk (Tamarix ramosissima, Tamarix chinensis, and their hybrids) and Russian olive (Elaeagnus angustifolia). These plants were introduced around 1900, and their success may be facilitated by river regulation, river channel changes, and precipitation patterns. We hypothesized that ripa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…However, a gap in hydrologic information prior to 1970 precluded a rigorous assessment of changes in these variables before and after the period of rapid population increase. Reynolds et al () reported rapid recruitment of Russian olive in Canyon de Chelly, AZ, beginning in 1983 and following a shift from a dry to a relatively wet period throughout the region that lasted from about 1978 to 1998 (Hereford, Webb, & Graham, ). Despite the lack of consistency in hydroclimate results between reaches in our study, the possible importance of regional climate shifts in Russian olive invasion patterns should not be discounted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a gap in hydrologic information prior to 1970 precluded a rigorous assessment of changes in these variables before and after the period of rapid population increase. Reynolds et al () reported rapid recruitment of Russian olive in Canyon de Chelly, AZ, beginning in 1983 and following a shift from a dry to a relatively wet period throughout the region that lasted from about 1978 to 1998 (Hereford, Webb, & Graham, ). Despite the lack of consistency in hydroclimate results between reaches in our study, the possible importance of regional climate shifts in Russian olive invasion patterns should not be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the south‐western United States, regional channel narrowing following both climate‐related drought and flow regulation has featured establishment and spread of the introduced riparian shrub tamarisk ( Tamarix ramosissima , Tsuga chinensis , and hybrids; Allred & Schmidt, ; Birken & Cooper, ; Hereford, ; Nagler, Glenn, Jarnevich, & Shafroth, ). More recently, Reynolds, Cooper, and Hobbs () document the invasion of tamarisk and Russian‐olive ( Elaeagnus angustifolia ), an introduced tree, along a south‐western U.S. stream with related channel narrowing. Generally speaking, whereas extensive research has been conducted on Tamarix spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geomorphic hardening of channel landforms would lead to decreases in sediment transport and channel migration. Channel narrowing has also been shown to coincide with Tamarix establishment [ Birken and Cooper , ; Everitt , ], although the direct influence of Tamarix on channelization is still debated [ Reynolds et al ., ]. In addition, Tamarix colonization often produced greater evaporation‐transpiration (ET) water losses due to expansion of riparian areas [ Hultine and Bush , ].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Russian-olive cover was unrelated to flow regulation or the degree to which flows were altered. Russian olive has established extensively along both regulated and largely unregulated river systems across the southwestern USA including Canyon de Chelly (Reynolds et al, 2014) and the Escalante River (Webb et al, 2007, M. Scott, unpublished data). These regional studies emphasize the notion that river regulation alone does little to explain the invasion of riparian ecosystems by non-native, woody species.…”
Section: Introductionmentioning
confidence: 99%